A study of Urban Heat Island relating "Local Climate Zones" using Landsat Images- The Case of Kathmandu Valley - Chettri, Deepak Bikram Thapa; Deo, Kusum; Regmi, Pukar (Himalayan Journal of Applied Science and Engineering, 2022)
Local Climate Zone (LCZ) classification has been intensively used in classification of urban and rural landscapes in the cities, which includes urban temperature studies. The urban heat island (UHI) in Kathmandu valley (Kathmandu, Bhaktapur, and Lalitpur), has been analyzed and standardized, which mainly focused on the Local Climate Zones (LCZs). The LCZs has distribute the landscape into homogeneous types on the basis of structural type, land surface cover, materials used, and into the anthropogenic activities. Such standardized classification has improved the meaning of urban research and made it easier to compare results among cities around the world. Landsat images, Google Earth, and SAGA-GIS software were used for creating LCZ map for Kathmandu for both March 2013 and March 2019 Landsat 8 TM/ETM+/OLI imagery was used to estimate land surface temperature (LST) For the estimation of LST world urban database and access portal tools (WUDAPT) algorithm was used considering emissivity. The result thus shows that the difference within the built-up scheme is around 2-4 °C whereas the difference between Building and Land cover types on the comparison is around 5-10°C. The disparity in building the land cover types shows that the UHI impact is present in the Kathmandu valley.